PENGEMBANGAN HANDOUT BERGAMBAR DISERTAI PETA KONSEP PADA MATERI KEANEKARAGAMAN HAYATI UNTUK SISWA SMA KELAS X - Anggraini, Siska; Sudirman, Sudirman; Nerita, S.Pd, M.Pd, Siska (STKIP PGRI Sumbar, 2014)
Media of learning is very important in teaching learning process, each of media is teaching material. The teaching material that using by the teacher is handout. Handout that using in the school is less in terest, in view of picture because the picture have not a colour, so, do not can in terest the students attention in learning. Based on that case, developed the media of learning such a pictorial handout with mind map in biological variety material for SMA class X. The purpose of this research is to know the validity and practicalities a pictorial handout with mind map. This research is development research that using model 4-D that consists of: Define, Design, Development and Disseminate. The Disseminate step do not conduct because of the limitation of the researcher. Subject of the research consist of 4 validators and practicalities test conducted by 2 teacher and 20 students of SMAN 1 Lengayang second grade class XI-IPA3. The result of validity test pictorial handout with mind map by validators, indicated that pictorial handout with mind map was valid criteria, that is 86,74%, in terms of didaktik aspect, contruction and technigue. The result of practicalities test a pictorial handout with mind map by the teacher showed that pictorial handout with mind map in practical criteria, that is 86,38%, from the practicalities students test84,99% in practical criteria. Based on the result of the research with mind map in Biological variety maretial for SMA first grade class X that have been resulted valid and practical.